The shifting allocation of authority in international law : considering sovereignty, supremacy and subsidiarity ; essays in honour of Professor Ruth Lapidoth /: considering sovereignty, supremacy and subsidiarity ; essays in honour of Professor Ruth Lapidoth. (2008) - Unknown
No abstract available